Efektifitas Konsentrasi Ragi Tape Terhadap Karakteristik Bioetanol: %Kemurnian, Ph, Dan Nilai Brix Hasil Dari Fermentasi Nira Tebu (Saccharum Officinarum) - Shafwan Amrullah; Khusnul Khatimah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2021)
Currently, fossil energy is the spearhead of Indonesia's energy needs and even the world. The fossil energy in question includes gasoline, natural gas and coal. This is due to the increasing population growth, even though energy reserves in Indonesia and even in the world continue to run low. So it is necessary to have alternative fuels such as bioethanol, which is a renewable fuel, especially from sugar cane juice. So this study aims to see the effect of the amount of yeast tape content on the characteristics of the bioethanol product produced. This type of research is experimental using a completely randomized design using 1 factor (the concentration of tape yeast is 5%, 10%, 15%).The results of this study indicate that there is an effect on the amount of tape concentration used as an active ingredient on the bioethanol product produced. The highest bioethanol content obtained from this fermentation result is the best at 15% tape yeast concentration, namely with an average of 6.67%, with an average pH of 3.3 and Brix 6%. Meanwhile, the lowest bioethanol content was obtained from the addition of 5% tape yeast concentration with an average of 3.67%, with an average pH of 3.13 and 5% brix.